Caracterização físico-química da biomassa produzida em sistemas florestais de curta rotação para geração de energia - Eufrade Junior, Humberto de Jesus [UNESP] (2015)
Bioenergy is one of the alternatives to reduce the dependence of global energy on fossil fuels. In recent years, several agencies and research centers, mainly in Europe and the United States, are encouraging projects for energy production from biomass. The short rotation forestry (SRF) appears as an interesting option for biomass production in a short time (1-3 years after planting). Currently, this biomass is used as chips for direct burning in boilers or processed as briquettes and pellets. The main objective of the research was to characterize the physical and chemical properties of the fractions of forest biomass to direct combustion, through analyses from ultimate, proximate and structural chemical compositions, macro and micronutrients, heating value, basic and energy density of wood. Additionally also evaluated the effect of spacing of planting and fertilizer dose on the properties: dry matter, energy potential and nutrient export. For this, a short rotation forestry of a hybrid clone (C219) of Eucalyptus urophylla x Eucalyptus grandis was studied in two different situations of plantation spacing (2,8m x 1,5m and 2,8m x 0,5m) and fertilizer levels. The collected biomass was fractionated into three parts: trunk, branches and leaves. Additionally, it was evaluated the effect of spacing of planting and fertilizer levels in properties, dry matter, energetic potential and nutrients exports. It was found that the spacing and fertilization had a little influenced in the physical and chemical properties of forest biomass and the largest difference occurred between the biomass fractions. Especially, the higher heating value (22,2 MJ.kg-1), extractives (37,9%) and ash (3,1%) of leaves compared with the wood that obtained 18,9 MJ.kg-1 for the higher heating value, 2% for extractives and 1,1% for ashes. For dry matter, energy potential and nutrients exports were more affected by variation factors ...